EVALUASI MEKANISME PENETAPAN CAPAIAN DALAM PROGRAM JAMKESMAS DI KOTA SEMARANG - Listyanto, Baskoro Anindya; Fathurrohman, Fathurrohman; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research analyze is it proper achievement in the program jamkesmas in helping poor people in the city of semarang. Operation of the concepts and an indicator of success ( in executing guidance jamkesmas 2012 ) of the theory of systems ( the process of ) according to Tatang m. Amirin, because what to evaluate in limited only the process of determination of the achievement of program jamkesmas in the city of semarang. And knowing the participation of stakeholders in setting targets JAMKESNAS Program in Semaran